PROSES PENGAMBILAN KEPUTUSAN PETANI DALAM PEMILIHAN JENIS TANAMAN BAWAH PADA KEBUN CAMPURAN (Decision-Making Processes of Farmers in Selecting Understorey Species in Mixed Garden) - Idin Saepudin Ruhimat (Balai Litbang Teknologi Agroforestry, Ciamis, 2020)
This study aims to analyze farmers' decision making in selecting understorey types in the sengon-based mixed garden. The research was conducted in Majenang District, Cilacap Regency, Central Java. Data were analyzed descriptively using Gladwin's real-life choice theory approach. The results of the study are as follows. First, thirteen main root crops make up the sengon-based mixed garden, namely: coffee, cocoa, cloves, coconut, petai, nutmeg, pepper, rubber, dukuh, pisitan, rambutan, soursop, and guava, as well as seven types of secondary root crops, namely: cardamom, cayenne pepper, banana, ginger, turmeric, cassava, and galangal. Second, the lower crops chosen by farmers based on five aspects of decision making were nutmeg and pepper for the main understorey, and cardamom and ginger for secondary understorey. Therefore, the lower plants that need to get priority to be cultivated in the development of mixed gardens in Majenang District, Cilacap Regency are nutmeg, pepper, cardamom and or ginger. The central and local governments need to facilitate the development of these mixed gardens.